2015
DOI: 10.1016/j.gene.2015.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of cardiac troponin C (TNNC1): Implications for heart failure, cardiomyopathies, and troponin modulating drugs

Abstract: In striated muscle, the protein troponin complex turns contraction on and off in a calcium-dependent manner. The calcium-sensing component of the complex is troponin C, which is expressed from the TNNC1 gene in both cardiac muscle and slow-twitch skeletal muscle (identical transcript in both tissues) and the TNNC2 gene in fast-twitch skeletal muscle. Cardiac troponin C (cTnC) is made up of two globular EF-hand domains connected by a flexible linker. The structural C-domain (cCTnC) contains two high affinity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 163 publications
(159 reference statements)
2
114
0
Order By: Relevance
“…Since dfbp-o and other compounds are known to bind to the interface between NTnC and TnI switch peptide[23], we developed a cardiac troponin C-troponin I chimera, cChimera, in which the switch region of cTnI is fused to the C terminus of cNTnC, building upon the previous design cNTnC-linker-switch peptide 144–173[21]. cChimera begins with residues 1 to 90 of human cNTnC (C35S, C84S), followed by residues 136–163 of cTnI (comprising the inhibitory 136–147 and switch 147–163 regions) and ending with a C-terminal His-tag.…”
Section: Methodsmentioning
confidence: 99%
“…Since dfbp-o and other compounds are known to bind to the interface between NTnC and TnI switch peptide[23], we developed a cardiac troponin C-troponin I chimera, cChimera, in which the switch region of cTnI is fused to the C terminus of cNTnC, building upon the previous design cNTnC-linker-switch peptide 144–173[21]. cChimera begins with residues 1 to 90 of human cNTnC (C35S, C84S), followed by residues 136–163 of cTnI (comprising the inhibitory 136–147 and switch 147–163 regions) and ending with a C-terminal His-tag.…”
Section: Methodsmentioning
confidence: 99%
“…Contraction is produced by sliding between the thick and thin filaments, a process that is powered by actin-activated myosin ATPase and regulated by cytosolic Ca 2+ via the troponin complex associated with the sarcomeric thin filament (Jin et al, 2008). Troponin I functions along with the other two subunits of troponin, troponin T (TnT) (Wei and Jin, 2011) and troponin C (TnC) (Li and Hwang, 2015), to govern muscle contraction and relaxation. To summarize the current knowledge on the TnI isoform genes and products, this review focuses on the evolution, gene regulation, posttranslational modifications, and structure-function relationship of TnI isoform proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As calcium channels in the heart are under the effect of sympathetic (βreceptors) and parasympathetic (muscarinicreceptors) modulation (Reuter, 1983), the aforementioned sympathetic activity will lead to an increase in Ca 2+ influx, contributing to the increase in myocardial contractility (Noble, 1984). Troponin C is the calciumbinding protein in the troponin complex in cardiomyocytes, where a rise in the intracellular Ca 2+ , with subsequent increased cTnC binding, is the event that initiates contraction in cardiac muscle (Li and Hwang, 2015). Hence it can be concluded that traumatic events can cause an increase in the cTnC expression through sympathetic stimulation and a subsequent increase in the in Ca 2+ influx into cardiomyocytes.…”
Section: Quantitative Morphometric Analysis For Immunohistochemical Cmentioning
confidence: 99%